Geographical distribution of Trypanosoma cruzi genotypes in Venezuela. - Hernán J Carrasco; Maikell Segovia; Martin S Llewellyn; Antonio Morocoima; Servio Urdaneta-Morales; Cinda Martínez; Clara E Martínez; Carlos Garcia; Marlenes Rodríguez; Raul Espinosa; Belkisyolé A de Noya; Zoraida Díaz-Bello; et al. (Public Library of Science (PLoS), 2012)
Chagas disease is an endemic zoonosis native to the Americas and is caused by the kinetoplastid protozoan parasite Trypanosoma cruzi. The parasite is also highly genetically diverse, with six discrete typing units (DTUs) reported TcI - TcVI. These DTUs broadly correlate with several epidemiogical, ecological and pathological features of Chagas disease. In this manuscript we report the most comprehensive evaluation to date of the genetic diversity of T. cruzi in Venezuela. The dataset includes 778 samples collected and genotyped over the last twelve years from multiple hosts and vectors, including nine wild and domestic mammalian host species, and seven species of triatomine bug, as well as from human sources. Most isolates (732) can be assigned to the TcI clade (94.1%); 24 to the TcIV group (3.1%) and 22 to TcIII (2.8%). Importantly, among the 95 isolates genotyped from human disease cases, 79% belonged to TcI - a DTU common in the Americas, however, 21% belonged to TcIV- a little known genotype previously thought to be rare in humans. Furthermore, were able to assign multiple oral Chagas diseases cases to TcI in the area around the capital, Caracas. We discuss our findings in the context of T. cruzi DTU distributions elsewhere in the Americas, and evaluate the impact they have on the future of Chagas disease control in Venezuela.